Modelling the effects of compression of fouling layers on the filtration performance of membrane bioreactors - Yala, Suzanne Akoth (Stellenbosch : Stellenbosch University, 2025)
Yala, S. A. 2025. Modelling the effects of compression of fouling layers on the filtration performance of membrane bioreactors. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/a524cbdc-94ef-4ce7-ab10-1e2301bc7bb2